2013
DOI: 10.3390/molecules18044651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Value and Appraisal of Polyphenols and Glucosinolates from Organic Baby-Leaf Salads as Antioxidants and Antimicrobials against Important Human Pathogenic Bacteria

Abstract: The present investigation has been carried out to investigate the biological role of four different types of baby-leaf salads and to study their potential as natural sources of antioxidants and antimicrobials against several isolates from important human pathogenic bacteria. Four single types of salads (green lettuce, red lettuce, rucola and watercress) and two mixtures [(1) red lettuce+green lettuce; (2) green lettuce + red lettuce + watercress + rucola] were assayed. The HPLC analysis revealed interesting le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Such active ingredients in GJ were also expected to disrupt the cell wall of gram-negative bacteria. Gram-negative bacteria have complex cell walls and are more resistant to antimicrobial agents than gram-positive bacteria [87,88]. Similar work has found that gram-positive bacteria were more susceptible to polyphenols than gram-negative bacteria.…”
Section: Nsdsc Protein Film Antimicrobial Activitymentioning
confidence: 77%
“…Such active ingredients in GJ were also expected to disrupt the cell wall of gram-negative bacteria. Gram-negative bacteria have complex cell walls and are more resistant to antimicrobial agents than gram-positive bacteria [87,88]. Similar work has found that gram-positive bacteria were more susceptible to polyphenols than gram-negative bacteria.…”
Section: Nsdsc Protein Film Antimicrobial Activitymentioning
confidence: 77%
“…In comparison to ampicillin, which demonstrated MICs of 0.1 and 3.2 μg/ml, Caffeic acid demonstrated an MIC of 1600 μg/ml against E. coli and S. aureus (Lim et al, 2016). Moreover, gallic acid has been shown to exhibit antibacterial properties against Enterococcus faecalis (Aires et al, 2013). It has also showed strong antibacterial potentials against Streptococcus pneumonia, P. aeruginosa, Moraxella catarrhalis, S. aureus, Enterococcus faecalis, E. coli, and Streptococcus agalactiae strains (Cueva et al, 2012).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…[ 40 ] Gallic acid is a phenolic acid showing an effect against Enterococcus faecalis . [ 41 ] It also showed the greatest effect, among several phenolic compounds, against a group of bacterial strains including Pseudomonas aeruginosa , S . aureus , Moraxella catarrhalis , E .…”
Section: In Vitro Antibacterial Activities Of Some Phenols Amentioning
confidence: 99%